Clinical protocol for nutritional screening in autism (PANA): a cross-sectional study protocol - Juliana dos Santos Vaz; Sandra Costa Valle; Eduarda De Souza Silva; Laura Vargas Hoffmann; Josiane Luçardo; Juliana Costa Maia; Luiza Vieira da Silva Magalhães; Kamila Castro (BMJ Open)
Introduction Autism spectrum disorder (ASD) is often accompanied by a variety of comorbidities. A high prevalence of patients has difficulties with food intake, which can lead to malnutrition, obesity and dyslipidaemia. Although several factors influencing dietary intake in this population have been investigated in the literature, the lack of standardised assessment protocols has led to heterogeneous results across studies. This study protocol describes the methodology used to assess nutritional aspects such as feeding problems, food intake and biochemical variables in children and adolescents with ASD.Methods and analysis The clinical protocol for nutritional screening in autism is a clinically based cross-sectional study design that focuses on the assessment of nutrition in children and adolescents with ASD aged 2 to under 19 years. Participants and caregivers are assessed in three clinical steps by a team of dietitians. Nutritional aspects are assessed, such as feeding behaviour (Brief Autism Mealtime Behavior Inventory, Children’s Eating Behavior Questionnaire), food intake (3 non-consecutive days of 24-hour food record), anthropometric measurements to calculate nutritional indicators according to WHO standards and blood samples (analysis of fasting glucose, triglycerides, total cholesterol and its subfractions). The data collected have the potential for descriptive and multivariate analyses to investigate associations among clinical, dietary difficulties, nutritional and biochemical variables.Ethics and dissemination The study protocol was approved by the institutional review board of the Federal University of Pelotas (CAEE: 94253518.0.0000.5317). The results will be disseminated through peer-reviewed publications and conferences.